Collective works, Festschrifts, series, symposia, etc. - The Editors, - (Nordic Archaeological Abstracts - NAA, 1982)
The list contains collective works, etc., the titles of which are followed by an asterix* in the abstract heading. Also, all series of Nordic material publications abstracted in this volume are listed.